Evaluasi dan Perbaikan Website SMA Negeri 01 Singosari dengan menggunakan Metode Human Centered Design (HCD) - Priska Aprillia Putri; Widhy Hayuhardhika Nugraha Putra; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Website for an educational institution is a must-have because the website is one of the information media that can be used to introduce the school to the public, this is done by SMA Negeri 01 Singosari. On the other hand there are things that need to be considered by the existence of the website, namely the usability or usability of the website. From the data obtained, there are still some complaints on the website of SMA Negeri 01 Singosari, among others, the lack of features such as sarpras, student attendance, student achievement and other factors such as the lack of responsiveness of the website so as to make users feel uncomfortable when using the website. Departing from the problem, evaluation and improvement of sma negeri 01 Singosari website using Human Centered Design (HCD) method was carried out. From the results of evaluation and improvement of the website using usability testing and SUS questionnaire, obtained the results of comparison of old websites and websites in terms of usability with details of effectiveness matrix increased on average up to 96%, efficiency matrix decreased from 1.944 seconds to 1.460 seconds, satisfaction matrix with awful category initial rating to good rating which means improvement of SMA Negeri 01 Singosari website can be said to be successful.